EVALUATING THE IMPACT OF MODERN ANTI-DIABETIC DRUGS ON SURVIVAL OUTCOMES IN LUNG CANCER PATIENTS WITH TYPE 2 DIABETES (Journal of Medical & Health Sciences Review, 2025)
With coexisting type 2 diabetes mellitus (T2DM) progressively understood as a variable affecting prognosis, lung cancer still ranks among the top causes of cancer-related death globally. Modern antidiabetic medications SGLT2 inhibitors, DPP4 inhibitors, and GLP1 receptor agonists have shown pleiotropic effects beyond glycemic control, therefore research on their involvement in cancer outcomes is under progress. In 150 lung cancer patients with T2DM, this cross sectional study examined the effect of contemporary antidiabetic medications on survival results. Structured clinical data and patient interviews were used to gather data over six months in tertiary hospitals. Statistical analysis with logistic regression and chisquare tests revealed (p < 0.05) that patients on contemporary antidiabetic medications showed considerably better survival trends than those on traditional therapies. These results promote the inclusion of modern diabetic management into oncological therapy for diabetic lung cancer patients.